Streptavidin-modified monodispersed magnetic poly(2-hydroxyethyl methacrylate) microspheres as solid support in DNA-based molecular protocols - Salih, Tagrid; Ahlford, Annika; Nilsson, Mats; Plichta, Zdeněk; Horák, Daniel (Materials science & engineering. C, Materials for biological applications, 2016)
Molecular diagnostics may provide tailored and cost efficient treatment for infectious disease and cancer. Rolling circle amplification (RCA) of padlock probes guarantees high specificity to identify nucleic acid targets down to single nucleotide resolution in a multiplex fashion. This makes the assay suitable for molecular analysis of various diseases, and interesting to integrate into automated devices for point-of-care analysis. A critical prerequisite for many molecular assays is (i) target-specific isolation from complex clinical samples and (ii) removal of reagents, inhibitors and contaminants between reaction steps. Efficient solid supports are therefore essential to enable multi-step, multi-analyte protocols. Superparamagnetic micro- and nanoparticles, with large surface area and rapid liquid-phase kinetics, are attractive for multi-step protocols. Recently, streptavidin-modified magnetic monodispersed poly(2-hydroxyethyl methacrylate) (STV-mag.PHEMA) microspheres were developed by multiple swelling polymerization. They are easily separated by a magnet and exhibit low non-specific protein sorption. In this study, the performance and the binding efficiency of STV-mag.PHEMA was addressed by circle-to-circle amplification (C2CA). A lower number of RCA products were detected as compared to the gold standard Dynabeads. Nevertheless, this study was the first to successfully adapt STV-mag.PHEMA microspheres as solid support in a DNA-based protocol, which is an important finding. The STV-mag.PHEMA microspheres were larger with about 16 times less surface area as compared to the Dynabeads, which might partly explain the lower rolling circle product (RCP) count obtained. Further research is currently ongoing comparing particles of similar sizes and optimizing reaction conditions to establish their full utility in the field. Ultimately, low cost and versatile particles are a great resource to facilitate future clinical molecular diagnostics.
Keywords: Microscopy, Electron, Scanning; Poly(2-hydroxyethyl methacrylate); spektroskopie infračervená s Fourierovou transformací; Streptavidin; DNA; mikroskopie elektronová rastrovací; Rolling circle amplification; Magnetics; streptavidin; Magnetic microspheres; Spectroscopy, Fourier Transform Infrared; Microspheres; magnetismus; imobilizované proteiny; Polyhydroxyethyl Methacrylate; polyhydroxyethylmethakrylát; Immobilized Proteins; Nucleic Acid Amplification Techniques; techniky amplifikace nukleových kyselin; mikrosféry